2017
DOI: 10.1007/978-3-319-53047-5_6
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Filaments Supporting Cell Shape and Growth in Bacteria

Abstract: For years intermediate filaments (IF), belonging to the third class of filamentous cytoskeletal proteins alongside microtubules and actin filaments, were thought to be exclusive to metazoan cells. Structurally these eukaryote IFs are very well defined, consisting of globular head and tail domains, which flank the central rod-domain. This central domain is dominated by an α-helical secondary structure predisposed to form the characteristic coiled-coil, parallel homo-dimer. These elementary dimers can further as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 186 publications
1
18
0
Order By: Relevance
“…FilP protein, which is associated with DivIVA, accumulates in the tips of young hyphae and is also expressed soon after germination starts ( Strakova et al, 2013a ). FilP resemble eukaryotic intermediate filaments forming a tangled cytoskeletal network that confers to rigidity and elasticity of hyphae ( Kelemen, 2017 ). The onset of these proteins was previously proposed as the point when the germination phase finalizes ( Strakova et al, 2013a ).…”
Section: Germination Stagesmentioning
confidence: 99%
“…FilP protein, which is associated with DivIVA, accumulates in the tips of young hyphae and is also expressed soon after germination starts ( Strakova et al, 2013a ). FilP resemble eukaryotic intermediate filaments forming a tangled cytoskeletal network that confers to rigidity and elasticity of hyphae ( Kelemen, 2017 ). The onset of these proteins was previously proposed as the point when the germination phase finalizes ( Strakova et al, 2013a ).…”
Section: Germination Stagesmentioning
confidence: 99%
“…IF proteins can be categorized in six subclasses based on their primary sequences: type I (acidic keratins), type II (neutral or basic keratins), type III (desmin, vimentin, GFAP), type IV (neurofilaments; NF-L, NF-M, and NF-H), type V (lamin A, B, and C), and type VI (nestin) (Stromer et al, 1987; Lendahl et al, 1990). All IFs share two major biochemical characteristics: first, their capacity to self-assemble in physiological buffers in the absence of cofactors (Godsel et al, 2008; Kelemen, 2017); second, the IF tripartite structural organization, comprising a conserved α-helical rod domain flanked by non–α-helical head and tail domains of different size, sequence, and function (Herrmann & Aebi, 2016; Kelemen, 2017). The α-helical domain of IF proteins form coiled-coil units that polymerize into non-polar filaments (Herrmann & Aebi, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, we found that Ni-NTA-bound Anabaena CCRPs readily precipitated upon transfer from denaturing to native buffer conditions, precluding further co-elution studies. Additionally, we observed that non-denaturing conditions failed to purify overexpressed CCRPs from E. coli , confirming their inherent insoluble nature, a property known to eukaryotic IFs 35 . Instead, we surveyed for further interaction partners by anti-GFP co-immunoprecipitation experiments of Anabaena cells expressing CeaR-GFP or LfiA-GFP and analyzed co-precipitated proteins by LC-MS/MS analytics (full list of possible interactiors in Supplementary File 3).…”
Section: Resultsmentioning
confidence: 58%
“…To predict potential filament-forming proteins, we performed a computational survey of the Anabaena genome for CCRPs putatively having IF-like function 8, 10, 11, 16 . Anabaena CCRPs were filtered according to the presence of a central rod-domain, which is characteristic to eukaryotic IF and prokaryotic IF-like proteins 35 . Similar to Bagchi et al .…”
Section: Resultsmentioning
confidence: 99%